Implementasi Konsep Tri Hita Karana Dalam Upaya Penguatan Nilai Gotong Royong Pada Sekha Teruna-teruni Mekar Sari - Putra, Kadek Dwi Sentana (Sphatika: Jurnal Teologi, 2024)
Tri Hita Karana is the concept of balance between humans and God, humans and each other, and humans and the environment. This concept is not about subjugating nature and each other, but rather becomes a harmonization between humans, who are called Bhuana Alit, and the universe, which is called Bhuana Agung. This concept of balance will lead to happiness or prosperity. This type of research is descriptive qualitative, using data collection techniques such as: observation, interviews, literature and documentation. The research entitled Implementation of the Tri Hita Karana Concept in Efforts to Strengthen Mutual Cooperation Values ​​in Sekha Teruna-Teruni Mekar Sari, Pakraman Apit Yeh Village, Bangli Village, Baturiti District, Tabanan, shows the efforts made by Sekha Teruna-Teruni Mekar Sari to strengthen the values mutual cooperation in every activity or work program carried out based on the Tri Hita Karana Concept. In the field of Prahyangan, efforts to strengthen the value of mutual cooperation are implemented through ngayah activities. In the Pawongan sector, to foster a sense of mutual cooperation, togetherness, building good interactions between Sekha Teruna-Teruni members is implemented through joy and sorrow programs and regular meetings. Lastly, in the Pabelasan sector, to foster a sense of unity, helping is carried out through routine community service activities every 2 weeks. Every activity from all elements of Tri Hita Karana is attempted to construct or stimulate the value of mutual cooperation.